Coated cutting tool with multi-layer composite structure and preparation method
By roughening the coating layer by layer during the preparation process of the multi-layer structure nanocomposite tool coating, the problem of poor coating bonding is solved and efficient mechanical properties and stability are achieved.
Patent Information
- Application Number
- CN202411796542.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing nanocomposite tool coating with multi-layer structures has poor coating bonding strength due to different compositions of each layer.
By performing roughening treatment after each target deposition and gradually reducing the degree of roughening treatment, the actual contact area between the layers is increased, providing more mechanical occlusion points, thereby enhancing coating bonding.
The excellent coating bonding and mechanical properties of the multi-layer composite structure coating tool are achieved, reducing the risk of coating cracking and improving overall stability.
Smart Images

Figure BDA0005176878290000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal cutting tools, and in particular to a coating tool with a multi-layer composite structure and a preparation method thereof. Background Art
[0002] Applying a hard coating on the tool surface by chemical vapor deposition (CVD) or physical vapor deposition (PVD) is an economical and effective way to improve the surface performance of the material. As an important branch of mechanical functional membranes, hard coatings are widely used in mechanical processing tools, especially in metal cutting. Hard coatings can improve the surface properties of materials, reduce friction and wear with workpieces, effectively improve the surface hardness, toughness, wear resistance and high temperature stability of materials, and greatly increase the service life of coating products.
[0003] In recent years, tool coating materials have been continuously upgraded and updated, and have experienced the development of simple binary coatings, ternary or quaternary solid solution coatings, multilayer or superlattice structure coatings, and nano-composite structure coatings. The hardness and maximum operating temperature of the coatings have been continuously improved. With the development of high-speed processing technology and various high-performance difficult-to-process materials, higher and higher requirements are placed on the performance of metal cutting tools.
[0004] Patent document CN105112858B discloses a multi-layer nano-composite tool coating, which includes a CrN bonding layer, an AlTiN transition layer, an AlTiN / TiSiN support layer and a TiSiN functional layer deposited on the surface of the tool substrate in sequence; the multi-layer nano-composite tool coating has high hardness and good wear resistance. However, due to the different compositions between the layers, the bonding force between the layers will be adversely affected. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a coated tool with a multi-layer composite structure and a preparation method thereof, so as to provide a coated tool with a multi-layer composite structure having excellent coating bonding strength.
[0006] Based on the above purpose, the present invention provides a method for preparing a coated tool with a multi-layer composite structure, and the specific preparation steps are as follows:
[0007] S1 substrate pretreatment: placing the substrate material in a vacuum coating device and heating it up for standby use;
[0008] S2 deposits a TiAIN layer: deposits a TiAIN layer on the surface of the substrate material, and after cooling, roughens it to a roughness of 0.8-1 μm;
[0009] S3 deposits a TiAIN+TiSiN layer: deposits a TiAIN+TiSiN layer on the surface of the TiAIN layer, and after cooling, roughens it to a roughness of 0.6-0.7 μm;
[0010] S4 deposits a TiAIN layer: deposits a TiAIN layer on the surface of the TiAIN+TiSiN layer, and after cooling, roughens it to a roughness of 0.4-0.5 μm;
[0011] S5: depositing a TiAIN+TiSiN layer: depositing a TiAIN+TiSiN layer on the surface of the TiAIN layer, and after cooling, roughening the layer to a roughness of 0.1-0.2 μm;
[0012] S6 deposits a TiSiN layer: deposits a TiSiN layer on the surface of the TiAIN+TiSiN layer, and after cooling, obtains a coated tool with a multi-layer composite structure.
[0013] Furthermore, the heating temperature in step S1 is 460-480°C.
[0014] Furthermore, the vacuum degree of the vacuum coating equipment in step S1 is 8×10 -5 mbar.
[0015] Furthermore, the base material in step S1 is a cemented carbide tool.
[0016] Furthermore, the conditions for depositing the TiAIN layer in step S2 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 2-3μm.
[0017] Furthermore, the roughening treatment in step S2 is performed by a sandblasting machine, using a sandblasting medium with a particle size of 50-100 μm, a sandblasting pressure of 0.4-0.6 MPa, and a sandblasting time of 30-60 s.
[0018] Furthermore, the conditions of the TiAIN+TiSiN layer in step S3 are as follows: the target materials are TiAI and TiSi target materials, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 1.5-2μm.
[0019] Furthermore, the TiAIN+TiSiN layer in step S3 is a periodic alternating deposition structure of TiAIN and TiSiN, and the number of alternating depositions is 10-30 times.
[0020] Furthermore, the roughening treatment in step S3 is performed by a sandblasting machine, using a sandblasting medium with a particle size of 30-50 μm, a sandblasting pressure of 0.3-0.5 MPa, and a sandblasting time of 20-40 s.
[0021] Furthermore, the conditions for depositing the TiAIN layer in step S4 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 0.8-1μm.
[0022] Furthermore, the roughening treatment in step S4 is performed by a sandblasting machine, using a sandblasting medium with a particle size of 20-30 μm, a sandblasting pressure of 0.2-0.4 MPa, and a sandblasting time of 10-30 s.
[0023] Furthermore, the conditions of the TiAIN+TiSiN layer in step S5 are as follows: the target materials are TiAI and TiSi target materials, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 1.5-2μm.
[0024] Furthermore, the TiAIN+TiSiN layer in step S5 is a periodic alternating deposition structure of TiAIN and TiSiN, and the number of alternating depositions is 10-30 times.
[0025] Furthermore, the roughening treatment in step S5 is performed by a sandblasting machine, using a sandblasting medium with a particle size of 10-20 μm, a sandblasting pressure of 0.1-0.2 MPa, and a sandblasting time of 5-15 s.
[0026] Furthermore, the conditions for depositing the TiAIN layer in step S6 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 0.5μm.
[0027] Furthermore, the roughening treatment is performed using a sandblasting machine.
[0028] Furthermore, the present invention also provides a coated tool with a multi-layer composite structure, wherein the coated tool with a multi-layer composite structure is prepared according to the above-mentioned method for preparing a coated tool with a multi-layer composite structure.
[0029] Beneficial effects of the present invention: In the process of preparing a multi-layer coated tool, the present invention performs a roughening treatment after each target material deposition, and the degree of each roughening treatment shows a decreasing trend, so that the actual contact area between the layers is further improved, and more mechanical bite points are provided, so that the coated tool has excellent coating bonding strength and mechanical properties.
[0030] The present invention performs a roughening treatment after each target material deposition during the process of preparing a multi-layer coated tool. Compared with the increasing trend of the degree of each roughening treatment and the same degree of each roughening treatment, the internal stress between the layers can be effectively dispersed and released, the risk of coating cracking can be reduced, the stress concentration at the interface can be reduced, and the overall stability of the coating can be improved, so that the final coated tool has excellent mechanical properties and coating bonding strength. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0032] Embodiment 1: A coated tool with a multi-layer composite structure, the specific preparation steps are as follows:
[0033] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 460 ° C;
[0034] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 1Pa, the bias voltage to 30VV, the arc source current to 200A, then open the TiAI target, deposit the TiAIN layer to a thickness of 2μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.8μm, wherein the particle size of the sandblasting medium is 50μm, the sandblasting pressure is 0.4MPa, and the sandblasting time is 30s;
[0035] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 1Pa, the bias voltage to 30VV, open the TiAI target, the arc source current to 200A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 200A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 10 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.6μm, wherein the particle size of the sandblasting medium is 30μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0036] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 1Pa, the bias voltage to 30VV, the arc source current to 200A, then open the TiAI target, deposit the TiAIN layer to a thickness of 0.8μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.4μm, wherein the particle size of the sandblasting medium is 20μm, the sandblasting pressure is 0.2MPa, and the sandblasting time is 10s;
[0037] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 1Pa, the bias voltage to 30VV, open the TiAI target, the arc source current to 200A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 200A, and deposit the AlTiN coating for 3min; alternately open and close the TiAI target and the TiSi target 10 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment to make the surface roughness 0.1μm, wherein the sandblasting medium particle size is 10μm, the sandblasting pressure is 0.1MPa, and the sandblasting time is 5s;
[0038] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 1 Pa, the bias voltage to 30 VV, and the arc source current to 200 A, then turn on the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled down to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0039] Embodiment 2: A coated tool with a multi-layer composite structure, the specific preparation steps are as follows:
[0040] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 470 ° C;
[0041] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 150V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 2.5μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.9μm, wherein the particle size of the sandblasting medium is 80μm, the sandblasting pressure is 0.5MPa, and the sandblasting time is 50s;
[0042] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 330A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.65μm, wherein the particle size of the sandblasting medium is 40μm, the sandblasting pressure is 0.4MPa, and the sandblasting time is 30s;
[0043] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 0.9μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0044] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 300A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the AlTiN coating for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.15μm, wherein the sandblasting medium particle size is 15μm, the sandblasting pressure is 0.15MPa, and the sandblasting time is 10s;
[0045] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 120 V, and the arc source current to 300 A, then turn on the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled down to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0046] Embodiment 3: A coated tool with a multi-layer composite structure, the specific preparation steps are as follows:
[0047] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 480 ° C;
[0048] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 5 Pa, the bias voltage to 200 V, the arc source current to 400 A, then open the TiAI target, deposit the TiAIN layer to a thickness of 3 μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 1 μm, wherein the particle size of the sandblasting medium is 100 μm, the sandblasting pressure is 0.6 MPa, and the sandblasting time is 60 s;
[0049] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 5Pa, the bias voltage to 200V, open the TiAI target, the arc source current to 400A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 400A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 30 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.7μm, wherein the particle size of the sandblasting medium is 0μm, the sandblasting pressure is 0.5MPa, and the sandblasting time is 40s;
[0050] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 5 Pa, the bias voltage to 200 V, the arc source current to 400 A, then open the TiAI target, deposit the TiAIN layer to a thickness of 1 μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.5 μm, wherein the particle size of the sandblasting medium is 30 μm, the sandblasting pressure is 0.4 MPa, and the sandblasting time is 30 s;
[0051] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 5Pa, the bias voltage to 200V, open the TiAI target, the arc source current to 400A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 400A, and deposit the AlTiN coating for 3min; alternately open and close the TiAI target and the TiSi target 30 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.2μm, wherein the sandblasting medium particle size is 20μm, the sandblasting pressure is 0.2MPa, and the sandblasting time is 15s;
[0052] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 5 Pa, the bias voltage to 200 V, and the arc source current to 400 A, then open the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0053] Comparative Example 1: A coated tool with a multi-layer composite structure, which is different from Example 2 in that the roughness of each roughening treatment is the same, and the specific preparation steps are as follows:
[0054] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 470 ° C;
[0055] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 150V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 2.5μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0056] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 330A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment to make the surface roughness 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0057] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 0.9μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0058] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 300A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the AlTiN coating for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment so that the surface roughness is 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0059] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 120 V, and the arc source current to 300 A, then turn on the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled down to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0060] Comparative Example 2: A coated tool with a multi-layer composite structure, which is different from Example 2 in that each roughening treatment has a gradient increasing trend, and the specific preparation steps are as follows:
[0061] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 470 ° C;
[0062] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 150V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 2.5μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.15μm, wherein the sandblasting medium particle size is 15μm, the sandblasting pressure is 0.15MPa, and the sandblasting time is 10s;
[0063] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 330A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment to make the surface roughness 0.45μm, wherein the particle size of the sandblasting medium is 25μm, the sandblasting pressure is 0.3MPa, and the sandblasting time is 20s;
[0064] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, the arc source current to 300A, then open the TiAI target, deposit the TiAIN layer to a thickness of 0.9μm, and after cooling, use a sandblaster to roughen the surface to a surface roughness of 0.65μm, wherein the particle size of the sandblasting medium is 40μm, the sandblasting pressure is 0.4MPa, and the sandblasting time is 30s;
[0065] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, open the TiAI target, the arc source current to 300A, deposit the TiAIN layer for 3min, then close the TiAI target, open the TiSi target again, adjust the arc source current to 300A, and deposit the AlTiN coating for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer is deposited. After cooling, a sandblasting machine is used for surface roughening treatment to make the surface roughness 0.9μm, wherein the particle size of the sandblasting medium is 80μm, the sandblasting pressure is 0.5MPa, and the sandblasting time is 50s;
[0066] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 120 V, and the arc source current to 300 A, then turn on the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled down to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0067] Comparative Example 3: A coated tool with a multi-layer composite structure, which is different from Example 2 in that no roughening treatment is performed. The specific preparation steps are as follows:
[0068] (1) Substrate pretreatment: Place the carbide tool material in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated for 1 h, so that the temperature rises to 470 ° C;
[0069] (2) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 150 V, the arc source current to 300 A, then open the TiAI target, and deposit a TiAIN layer with a thickness of 2.5 μm;
[0070] (3) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, turn on the TiAI target, the arc source current to 330A, deposit the TiAIN layer for 3min, then turn off the TiAI target, turn on the TiSi target, adjust the arc source current to 300A, and deposit the TiSiN layer for 3min; alternately open and close the TiAI target and the TiSi target 20 times, and the TiAIN+TiSiN layer deposition is completed;
[0071] (4) Deposition of TiAIN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 120 V, the arc source current to 300 A, then open the TiAI target, and deposit the TiAIN layer with a thickness of 0.9 μm;
[0072] (5) Deposition of TiAIN+TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3Pa, the bias voltage to 120V, turn on the TiAI target, set the arc source current to 300A, deposit the TiAIN layer for 3min, then turn off the TiAI target, turn on the TiSi target, adjust the arc source current to 300A, and deposit the AlTiN coating for 3min; alternately turn on and off the TiAI target and the TiSi target 20 times, and the deposition of the TiAIN+TiSiN layer is completed;
[0073] (6) Deposition of TiSiN layer: Open the N2 flow valve, adjust the coating pressure to 3 Pa, the bias voltage to 120 V, and the arc source current to 300 A, then turn on the TiSi target, and deposit a TiSiN layer with a thickness of 0.5 μm. The tool is cooled down to below 200 °C in the furnace and then taken out and cooled at room temperature to obtain a coated tool with a multi-layer composite structure.
[0074] Performance Testing
[0075] Coating adhesion: The scratch test was performed using an automatic scratch tester. The force loading speed was 100N / m, the scratch length was 5mm, and the final load was 100N. The test results are shown in Table 1.
[0076] Nanohardness: measured using a UNHT nanoindenter with the following parameters: maximum load 10 mN, loading rate 20 mN / min, unloading rate 20 mN / min, holding time 10 s. The test results are shown in Table 1.
[0077] Wear resistance: The test was conducted on a CK6140 horizontal lathe produced by Chongqing Honggang CNC Machine Tool Co., Ltd. The experimental standard was: each set of blades continuously fed 220 mm at 105 m / min until the feeding distance was L = 2200 mm, and the flank wear was measured. The test results are shown in Table 1.
[0078] Table 1 Performance test results
[0079]
[0080] From the data analysis, it can be seen from Examples 1-3 that the coated tool with a multi-layer composite structure of the present invention has excellent hardness and wear resistance. Its nanohardness can reach 35.51 GPa, and the minimum wear of the back tool surface can reach 0.12 mm. Most importantly, it has excellent coating adhesion, which can prevent the coating from falling off during cutting.
[0081] It can be seen from Example 2 and Comparative Examples 1, 2, and 3 that the present invention performs a roughening treatment after each target material deposition during the preparation of a multilayer coated tool, and the degree of each roughening treatment shows a decreasing trend, so that the coated tool has excellent coating adhesion and mechanical properties. This may be because the surface roughness of the coating is improved by the roughening treatment, thereby increasing the actual contact area and providing more mechanical bite points. At the same time, the roughened surface can form a gradually transitioning interface area, which helps to reduce stress concentration at the interface and can enhance the interface bonding effect between the layers, which helps to improve the bonding between the coating and the substrate; and, relative to the increasing trend of the degree of each roughening treatment and the same degree of each roughening treatment, the treatment method in which the degree of each roughening treatment shows a decreasing trend can effectively disperse and release the internal stress between the layers, reduce the risk of coating cracking, reduce stress concentration at the interface, and improve the overall stability of the coating, so that the final coated tool has excellent mechanical properties and coating adhesion.
[0082] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a coated tool having a multi-layer composite structure, characterized in that: The specific preparation steps are as follows: S1 substrate pretreatment: placing the substrate material in a vacuum coating device and heating it up for standby use; S2 deposits a TiAIN layer: deposits a TiAIN layer on the surface of the substrate material, and after cooling, roughens it to a roughness of 0.8-1 μm; S3 deposits a TiAIN+TiSiN layer: deposits a TiAIN+TiSiN layer on the surface of the TiAIN layer, and after cooling, roughens it to a roughness of 0.6-0.7 μm; S4 deposits a TiAIN layer: deposits a TiAIN layer on the surface of the TiAIN+TiSiN layer, and after cooling, roughens it to a roughness of 0.4-0.5 μm; S5: depositing a TiAIN+TiSiN layer: depositing a TiAIN+TiSiN layer on the surface of the TiAIN layer, and after cooling, roughening the layer to a roughness of 0.1-0.2 μm; S6 deposits a TiSiN layer: deposits a TiSiN layer on the surface of the TiAIN+TiSiN layer, and after cooling, obtains a coated tool with a multi-layer composite structure.
2. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The temperature of the heating in step S1 is 460-480°C.
3. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The conditions for depositing the TiAIN layer in step S2 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 2-3μm.
4. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The conditions of the TiAIN+TiSiN layer in step S3 are as follows: the target materials are TiAI and TiSi target materials, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 1.5-2μm.
5. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The conditions for depositing the TiAIN layer in step S4 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 0.8-1μm.
6. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The conditions of the TiAIN+TiSiN layer in step S5 are as follows: the target materials are TiAI and TiSi target materials, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 1.5-2μm.
7. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The conditions for depositing the TiAIN layer in step S6 are as follows: the target material is TiAI, the introduced gas is N2, the coating pressure is adjusted to 1-5Pa, the bias voltage is adjusted to 30V-200V, the arc source current is 200-400A, and the deposition thickness is 0.5μm.
8. The method for preparing a coated tool with a multi-layer composite structure according to claim 1, characterized in that: The roughening treatment is performed by using a sandblasting machine.
9. A coated tool with a multi-layer composite structure, characterized in that: The coated tool with a multi-layer composite structure is prepared according to the method for preparing a coated tool with a multi-layer composite structure according to any one of claims 1-8.
Citation Information
Patent Citations
A nano-composite tool coating with a multi-layer structure
CN105112858B
Cited By
A diamond multilayer composite cutter and a method for manufacturing the same
CN122787429A